The Effect of Earnings Management, Financial Ratios, and Corporate Governance Mechanisms on Bond Ratings - Muhammad Rusli; Andi Firdania; Andi Masniah (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Introduction: Bond ratings are key indicators of corporate credit risk and reduce information asymmetry in debt markets. In Indonesia, PT PEFINDO ratings differentiate issuers with stronger credit quality (investment grade) from riskier issuers (non-investment grade). This study examines whether earnings management, financial ratios, and corporate governance mechanisms affect bond ratings of IDX-listed issuers rated by PEFINDO. Material and Methods: This quantitative explanatory study uses secondary data from annual reports/financial statements and PEFINDO bond ratings. Using purposive sampling, 11 non-financial firms were observed for 2018–2022 (44 firm-year observations). Bond ratings were coded as a binary variable (investment grade = 1; non-investment grade = 0) and analyzed using binary logistic regression. Research Results: Most observations were investment grade (59.1%). The model fits well (Hosmer–Lemeshow Sig. = 0.907) with strong explanatory power (Nagelkerke R² = 0.795). Earnings management negatively affects the probability of achieving investment grade, while liquidity, managerial ownership, and audit quality (Big-4 proxy) positively affect it. Total asset turnover, price–earnings ratio, institutional ownership, and independent commissioners are not significant. Conclusion: Bond ratings are more closely related to reporting credibility, liquidity strength, and selected governance signals than to market-based and activity ratios in this sample. Issuers should enhance reporting quality, liquidity management, and audit/governance credibility to support higher bond ratings; future studies should expand samples, periods, and include additional credit-risk controls and alternative rating models.